1963
DOI: 10.1152/jappl.1963.18.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Diving pattern, lung volumes, and alveolar gas of the Korean diving woman (ama)

Abstract: Lung volumes and alveolar gases during actual dives were studied in the Korean diving women, or ama. These women dive without assistance. Average descent and ascent velocities are 0.6 m/sec. Maximal depth and duration of dive observed were 17 m and 82 sec, respectively. However, typical sustained diving activity is to a depth of 5 m for 30 sec, averaging 60 dives/hr. This diving pattern is compared with the assisted dives of the Japanese ama lasting 60 sec and reaching a depth of about 20 m. Prior to diving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…in Ama, who lost adaptation to cold when they started using wet suits [5]. Yet Ama did not show increased lung volumes despite their long-lasting diving activity [18,19], and it is a common notion in exercise physiology that lung volumes cannot be trained [20]. Nevertheless Clanton et al [21] found a significant increase in VC and TLC in a group of competitive female swimmers, who underwent a specific inspiratory muscle training regimen beside their usual swimming training.…”
Section: Discussionmentioning
confidence: 99%
“…in Ama, who lost adaptation to cold when they started using wet suits [5]. Yet Ama did not show increased lung volumes despite their long-lasting diving activity [18,19], and it is a common notion in exercise physiology that lung volumes cannot be trained [20]. Nevertheless Clanton et al [21] found a significant increase in VC and TLC in a group of competitive female swimmers, who underwent a specific inspiratory muscle training regimen beside their usual swimming training.…”
Section: Discussionmentioning
confidence: 99%
“…BYRNE-QUINN et al(1971)re-ported that trained athletes exhibited lower ventilatory response to hypoxia than non-athletes.This could be the case in the Ama who are required to do severe physical work in their daily diving.Another way to explain the lower hypoxic sensitivity of the divers is chronic exposure to hypoxia. HONG et al(1963)andreported that the alveolar Po2 of the breath-hold divers decreased when ascending from a dive.Thus,the Ama are exposed to rapid hypoxia in repeated daily diving. WEIL et al(1971)observed that chronic exposure to hypoxia during adulthood in man resulted in marked attenuation of the ventilatory response to hypoxia at rest and this was a function of the length of exposure to hypoxia.Therefore,it can be speculated that the Ama have acquired low hypoxic sensitivity by both chronic exposure to hypoxia and severe physical work in their daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the CO2-response slope between Ama (Kachido)and controls. SONG et al(1963)reported a comparable observation that the absolute magnitude of ventilation in CO2-response did not differ between the Hae-Nyo(corresponding to the Kachido in Korea)and Korean housewives , but the ventilatory response relative to the normal ventilation,VER,in hypercapnia of Hae-Nyo was 0.86 times that of the control.On the other hand,the Funado (who has a helper in a boat and dives deeper and for longer than the Kachido) showed reduced sensitivity to hypercapnia in our experiment conducted with the same experimental procedures(unpublished data).Thus,it seems important how deep and for how long the divers are involved in their daily diving .The Funado dives deeper and for longer than the Kachido,with the former group showing lower sensitivity to hypercapnia than the latter.According to the reports of the alveolar gas composition during breath-hold diving (LANPHIER and RAHN ,1963;HONG et al,1963),the divers are exposed to hypercapnia while working at the bottom of each dive.The Funado are exposed to a more hypercapnic condition than the Kachido because of deeper and longer diving.In addition to the alveolar gas composition and diving patterns,it was reported that ventilatory response to hypercapnia was related to physical training.BYRNE-QUINN et al . Vol.31,No.2,1981 Y.HONDA ( )and LALLY et al(1974reported that well-trained athletes showed reduced sensitivity to hypercapnia at rest and during exercise.Therefore,it is possible that the Ama obtained decreased hypercapnic sensitivity by repeated exposure to hypercapnia in daily diving as well as by their concomitant daily physical stress and conditioning.Judging from their diving pattern,Kachido would be exposed to mild hypercapnic stress and thus they should have shown relatively weak adaptation to hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the dive, they were pulled up with a rope by a man on a boat above (Hong and Rahn 1967). This procedure reduces considerably the energy cost of diving with respect to the unassisted technique, so that the Funado can perform longer (60 s instead of 30 s) and deeper (20 m instead of 5 m) dives than unassisted divers (Cachido; Hong et al 1963). The time spent at the bottom was some 25% of the total diving duration.…”
Section: Introductionmentioning
confidence: 99%